Fabrication of Large-Area High-Resolution Templates by Focused Ion Beam Combined with Colloidal Nanoparticle Dimer Deposition for SERS Substrates - Liga Ignatane; Reinis Ignatans; Juris Prikulis; Annamarija Trausa; Ciro Federico Tipaldi; Edgars Vanags; Martins Zubkins; Krisjanis Smits; Anatolijs Sarakovskis (Nanomaterials)
This article presents an examination of well-controlled patterns created using a Ga+-based focused ion beam (FIB) on glass, while silicon substrates were used to evaluate the FIB performance by its achievable feature size versus time constraints. The pattern creation on glass was developed with the aim of studying potential surface-enhanced Raman spectroscopy (SERS) applications. Furthermore, the FIB was used to create dimer systems of periodically and randomly positioned dumbbell-shaped pits on the glass (each dimer occupies an area of 203 × 87 nm2). By following the bitmap pattern files, the FIB ensured there was 3000 dimer fabrication over a 20 × 20 μm2 large area, with a pit size and position variation below 10 nm. The article highlights that FIB can be used for precise large-area nano-fabrication. The gold nanoparticle dimers were formed on the prepatterned surface via capillary force-assisted deposition. The fabricated nanostructures were tested in SERS measurements. The enhancement factor for Rhodamine B molecule reached ~105, demonstrating the potential application of the method to create nanostructures in the sensor domain.